Knowledge and practice of computed tomography exposure parameters amongst radiographers in Jordan. (1st November 2018) - Rawashdeh, Mohammad; McEntee, Mark F.; Zaitoun, Maha; Abdelrahman, Mostafa; Brennan, Patrick; Alewaidat, Haytham; Lewis, Sarah; Saade, Charbel
Abstract: Objective: To investigate the knowledge and practice of computed tomography (CT) radiographers working in Jordan. Materials and methods: This Institutional Review Board (IRB) approved study disseminated a questionnaire via social media and recruited 54 Jordanian CT radiographers. The questionnaire comprised 36 questions divided into four sections: demographics; an evaluation of knowledge regarding CT exposure; modifications to CT exposure for paediatric patients; dose units and diagnostic reference levels (DRLs). Descriptive and inferential statistics including Chi-square tests, Mann–Whitney U tests, independent samples t-tests and Kruskal–Wallis H tests were employed. Statistical significance was considered below p < 0.05. Results: The 54 participants had various qualifications, with the majority holding a Bachelor's degree (n = 35, 64.8%) and the rest holding a Diploma (n = 19, 35.2%). In order to pass the questionnaire, participants needed to score 13 correct answers. The overall number of radiographers who correctly passed the questionnaire was 48 (88.9%). None of the participants correctly stated all the DRL values for chest, abdomen and brain CT. However, four out of 54 respondents (7.4%) knew the chest DRL value, three (5.6%) participants correctly estimated the abdominal DRL value but only two (3.7%) knew the DRL for the brain. Conclusion: Good general knowledge was found amongst radiographers regarding the relationship of each exposure parameter to the image quality and patient dose. However, there was poor knowledge of diagnostic reference levels and the order of the organ radiation sensitivity. The need for CT radiographers to undertake further education that focuses on radiation exposure in CT is highlighted. Highlights: CT radiographers need to understand parameter modification in order to optimise patient dose. The influence of some CT parameters is not fully understood. A need for on-going education in dose reduction is required.